Anatomy-guided resections for paralimbic tumors in the temporo-insular region: combining tumor and epilepsy surgery concepts - Alkassm, Emad; Grote, Alexander; Berger, Björn; Woermann, Friedrich G.; Ersoy, Tunc Faik; Coras, Roland; Kalbhenn, Thilo; Simon, Matthias (Frontiers in Neurology, 2024)
Object Tumors in the temporo-mesial region often extend into the insula and vice versa. The present study investigated the results of a surgical strategy that combines principles of tumor and epilepsy surgery. Methods We retrospectively analyzed 157 consecutive patients with intrinsic brain tumors in the temporo-mesial region, with varying degrees of extensions into the insula (44 patients, 28.0%). The surgical strategy utilized “anatomy-guided resection,” targeting specific anatomical compartments infiltrated by the tumor (e.g., temporal pole, anterior temporo-mesial region = uncus and hippocampal head, posterior temporo-mesial, insula) rather than treating the tumor as a single mass. Results The most frequent histologies were ganglioglioma CNS WHO grade 1 (55 patients, 35.0%) and IDH1 wildtype glioblastoma (36 patients, 22.9%). Tumor infiltration was most commonly found in the anterior temporo-mesial compartment (145 patients, 92.4%). An anterior temporal lobectomy was part of the surgical strategy in 131 cases (83.4%). Seventy-six patients (48.4%) with drug-resistant epilepsy underwent a formal presurgical epilepsy work-up, including depth electrode placement in three cases. Complete resections were achieved in 117 patients (74.5%), with supramarginal resections performed in 89 cases (56.7%). Four patients experienced non-temporary neurological complications (CTCAE grade 3–5). At 6 months, 127 of 147 assessable patients (86.4%) were free from seizures or auras (ILAE class 1), excluding early postoperative seizures (<30 days). At 24 months, 122 of 144 assessable cases (84.7%) remained seizure-free (ILAE class 1). Kaplan–Meier estimates for 5-year overall survival were 98.5% for non-recurrent glioneuronal tumors. The 2-year overall survival estimates were 96.0% for 24 primary diffuse CNS WHO grade 2 and 3 gliomas and 55.2% for 30 patients undergoing first surgeries for glioblastomas/astrocytomas CNS WHO grade 4. Conclusion Combining both epilepsy and tumor surgery concepts in the surgical treatment of intrinsic brain tumors involving the mesial temporal lobe, often extending into the insula, led to more extensive resections, improved seizure outcomes, and potentially even better patient survival outcomes.